Analisis Toleransi Beragama di Kalangan Mahasiswa Universitas Muhammadiyah Maumere - Arjuna Al Ayubi Wende; Bernaditha Agustan Dua Bura; Faisal Dermawan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study aims to analyze the level of religious tolerance among students at the University of Muhammadiyah Maumere. Using a qualitative approach with interview, observation, and questionnaire methods, this study revealed that although the majority of students understand the concept of religious tolerance, there are differences in its application in everyday life. Family factors and academic environment play an important role in shaping students' tolerant attitudes. The results of the study indicate that the campus environment is quite conducive with little potential for inter-religious conflict, but there are still challenges in the initial interactions of new students. The University of Muhammadiyah Maumere shows a commitment to promoting tolerance through inclusive academic policies and social activities, strengthening harmonious relationships between students from various religious backgrounds.